The Use of TikTok as an Alternative Medium for Arabic Language Learning Among STIQ Students - Zakiah, Nor; Zubaidillah, Muh. Haris; Iqbal, Muhammad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Social media development has opened new opportunities in education, including Arabic language learning. One platform widely used by university students is TikTok, which provides short audio-visual video content. This study aims to describe the use of TikTok as an alternative medium for Arabic language learning, students’ experiences, and the supporting and inhibiting factors faced by STIQ Amuntai students. This research employed a qualitative approach with a descriptive method. Data were collected through interviews with five STIQ Amuntai students who actively used TikTok in Arabic language learning. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that TikTok was utilized as a supporting medium for Arabic learning by following educational accounts that presented vocabulary (mufradāt), daily conversations (muḥādatsah), pronunciation, and basic nahwu and sharaf rules. Students’ experiences showed positive responses because the short, engaging, and audio-visual materials helped improve their understanding and proficiency in Arabic, especially in vocabulary, listening, and speaking skills. Supporting factors included ease of access, the abundance of educational content, and creative material presentation. Meanwhile, inhibiting factors included limited depth of material, lack of systematic presentation, and distractions from entertainment content. Therefore, TikTok has the potential to serve as an alternative learning medium.